2021
DOI: 10.4236/wjet.2021.93033
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Car-Following Model Based on the Random Forest

Abstract: The car-following models are the research basis of traffic flow theory and microscopic traffic simulation. Among the previous work, the theory-driven models are dominant, while the data-driven ones are relatively rare. In recent years, the related technologies of Intelligent Transportation System (ITS) represented by the Vehicles to Everything (V2X) technology have been developing rapidly. Utilizing the related technologies of ITS, the large-scale vehicle microscopic trajectory data with high quality can be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Some researchers have developed data-driven car-following models that can replace mathematical models. For instance, Shi et al developed a data-driven car-following model using random forest, and showed that the model could better predict car-following behavior than the GM model (18). Hao (20).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have developed data-driven car-following models that can replace mathematical models. For instance, Shi et al developed a data-driven car-following model using random forest, and showed that the model could better predict car-following behavior than the GM model (18). Hao (20).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers have developed data-driven car-following models that can replace mathematical models. For instance, Shi et al developed a data-driven car-following model using random forest, and showed that the model could better predict car-following behavior than the GM model ( 18 ). Hao et al developed a data-driven car-following model based on rough set theory ( 19 ), and Zhang et al developed a model based on genetic algorithms ( 20 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the advancement of innovative technologies in an era of big data, there are other approaches to evaluating performance for providing critical information on transportation systems, for instance, modeling car-following behavior under multiple performance indicators [15] and utilizing connected vehicle data to assess the performance and operation of transportation infrastructures, such as interchanges [16] and pavement conditions [14] [17] [18].…”
Section: Performance Measurementmentioning
confidence: 99%
“…It can be seen from the above literature that the accuracy of driving behavior recognition varies widely, which is closely related to sensor data fusion and feature extraction. Some scholars also use the random forest model to identify driving behaviors such as car-following [50,51], lane change [8], and being followed [9] or to evaluate driving safety risks [10] and identify drivers [52,53], driving style [54], and driving posture [55]. Other researchers [56] combined random forest and other methods to construct a driving behavior recognition model.…”
Section: The Recognition Model Of Driving Behaviormentioning
confidence: 99%
“…Distracted driving [7] [49] Used for distracted driving behavior recognition Car-following [50] [51] Used for identification of following driving behavior Lane change [8] [56] Used for lane change driving behavior recognition Others [9,10] [52] [53][54][55] Used for acceleration and deceleration, turning, lane change, being followed, and driver, driving style, driving posture recognition 6 Journal of Advanced Transportation application fields and corresponding advantages and disadvantages is shown in Table 3.…”
Section: Types Of Driving Behavior Applications Advantages and Disadv...mentioning
confidence: 99%